PROPOSED IMPROVEMENT OF YARN PRODUCT QUALITY USING THE KIPLING METHOD - Robecca, Julian; Sagathi, Malda (Teknik Industri Unikom, 2020)
This journal presents research on improving product quality in a company. This study aims to identify the factors that cause disability in a product and propose follow-up solutions in order to improve the quality of a product. The method used in the study is the fishbone diagram and the Kipling method (5W + 1H) to improve product quality. The product under study is a yarn product manufactured in the second building of the company. There are 8 types of product defects that cause product quality to decline and are not suitable for sale, which can result in losses to the company, which are not good spools, dirty spools, yarn spools of different diameters, spools of cross yarn, spools of loose yarn, defective cones, incorrect cone types and the weight of the yarn is distorted. From all types of defects, the result shows that the most defects are in the category of bad roll defects of 31%, with the number of defective products of 215 spools of the total defective products of 716 spools. After conducting research, it was concluded that product defects occur due to lack of machine maintenance, mistakes from operators when installing the machine. If the company can reduce the occurrence of defects or damage to the yarn product, it will benefit a lot.